2023
DOI: 10.3389/fpubh.2023.1085991
|View full text |Cite
|
Sign up to set email alerts
|

Lag-time effects of vaccination on SARS-CoV-2 dynamics in German hospitals and intensive-care units

Abstract: BackgroundThe Efficacy and effectiveness of vaccination against SARS-CoV-2 have clearly been shown by randomized trials and observational studies. Despite these successes on the individual level, vaccination of the population is essential to relieving hospitals and intensive care units. In this context, understanding the effects of vaccination and its lag-time on the population-level dynamics becomes necessary to adapt the vaccination campaigns and prepare for future pandemics.MethodsThis work applied a quasi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The foregoing is not intended to downplay the benefit of HCW COVID-19 vaccination in reducing time loss, which has been reported in other studies, including those by Maltezou et al and Paladino and colleagues. In addition, the literature has highlighted the importance of vaccination for the whole population, with lower hospital and intensive care patient numbers associated with high vaccine coverage ( 38 ). Specifically that study found that vaccination provided a significant protective effect when at least 40% of people are vaccinated, whatever the dose considered ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The foregoing is not intended to downplay the benefit of HCW COVID-19 vaccination in reducing time loss, which has been reported in other studies, including those by Maltezou et al and Paladino and colleagues. In addition, the literature has highlighted the importance of vaccination for the whole population, with lower hospital and intensive care patient numbers associated with high vaccine coverage ( 38 ). Specifically that study found that vaccination provided a significant protective effect when at least 40% of people are vaccinated, whatever the dose considered ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the literature has highlighted the importance of vaccination for the whole population, with lower hospital and intensive care patient numbers associated with high vaccine coverage ( 38 ). Specifically that study found that vaccination provided a significant protective effect when at least 40% of people are vaccinated, whatever the dose considered ( 38 ).…”
Section: Discussionmentioning
confidence: 99%